Biochemical and Hematological Assessment in Patients With Thyroid Dysfunction - Kadhum, Nadia. H. (Medicra (Journal of Medical Laboratory Science/Technology), 2024)
This investigation conducted for biochemical and hematological assessment in patients with thyroid dysfunction. The research was carried out at a laboratory in Baghdad, Iraq, and it is a case-control study. The sample was gathered from February 2023 through the years 2021 and 2022. About 250 individuals were a part of this study; 100 were hypothyroid, 100 were hyperthyroid, and 50 had normal thyroid function and complete blood counts. A total of three millilitres of whole blood and two millilitres of EDTA were obtained from each subject in an aseptic manner for the CBC. Also, 2 ml of blood was drawn for serum separation, these sera were used for evaluation T3, T4, TSH, AST, ALT, Urea and Creatinine by using kits purchased from Linear company, the procedures for all were done according to manufacturer instructions. The control group had considerably greater mean RBC, Hb, HCT, and MCH concentrations, while the hypothyroid group had significantly lower values. The hyperthyroid group showed no significant difference between MCV and MCH. There were no statistically significant MCHC results in either the hypothyroid or hyperthyroid groups compared to the control group. There was little difference in total lymphocyte and platelet counts between the control, hyperthyroid, and hypothyroid groups. Differential leukocyte count showed statistically significant differences between the hypothyroid and hyperthyroid groups. As seen in Table 2, the hypothyroid group had higher serum TSH levels (p<0.05), in contrast to the hyperthyroid group which exhibited lower levels (p<0.05). Alternatively, when contrasted with the control group, the hypothyroid group had lower T3 and T4 levels (p<0.05), whereas the hyperthyroid group had higher levels (p<0.05). Improvements in hepatic and kidney functions were seen in patients with hypo or hyperthyroidism as compared to the control group in this investigation. In conclusion, both hypothyroidism as well as hyperthyroidism affects on hematological and biomarkers for thyroid, liver and kidney